Science, Technology and Skills - Pardey, Philip; James, Jennifer; Alston, Julian; Wood, Stanley; Koo, Bonwoo; Binenbaum, Eran; Hurley, Terrance; Glewwe, Paul (Washington, DC: World Bank, 2012)
Improvements in agricultural productivity have alleviated much poverty and starvation and fuelled economic progress. However, comparatively little agricultural R&D and "technology tailoring" has been done for the conditions confronting African agriculture. Innovation in African agriculture and other regions of the developing world will be critical to solving the scourge of hunger and lifting the lot of the billions of the world's people who rely on agriculture for a living, and the entire world's poor who rely on agriculture for their sustenance. A shift in R&D agendas is forcing a rethinking of national and multinational policies. National governments can tailor the institutional and policy details of Intellectual Property Rights to best fit local circumstances; increase the total amount of government funding for their national agricultural R&D systems; introduce institutional arrangements and incentives for private and joint public-private funding; and improve the processes by which agricultural R&D resources are administered and allocated.